Pengaruh Perceived Experiential Branding dan Social Buzz terhadap FOMO serta Purchase Intention Konsumen Cloudcakes di TikTok - Bianca Ayu Anindira; Adnan Kasofi; Osly Usman; Ryna Parlyna (Journal of Strategic Marketing and Innovation, 2026)
This study investigates how Perceived Experiential Branding (PEB) and Social Buzz (SB) influence Purchase Intention (PI) toward Cloudcakes as a viral local F&B brand on TikTok, with Fear of Missing Out (FOMO) as a mediating variable within the Stimulus–Organism–Response (S–O–R) framework. A quantitative explanatory design was employed using an online survey of Indonesian TikTok users who have been exposed to Cloudcakes-related content. Data were analyzed using SEM-PLS. The preliminary adequacy test indicates the dataset is suitable for factor-based modeling (KMO = 0.957; Bartlett’s test significant). Measurement model results demonstrate strong reliability and convergent validity, supported by high internal consistency and satisfactory indicator loadings, as well as established discriminant validity. Structural model testing shows that PEB and SB significantly increase FOMO, and both PEB and SB also positively affect PI. FOMO further strengthens PI, confirming its mediating role. The model explains substantial variance in FOMO and PI and demonstrates predictive relevance. These findings imply that local F&B brands can enhance purchase intention by strengthening experiential branding and maintaining social buzz while managing FOMO-driven pressure responsibly.